Formation of disinfection by-products during chlorine dioxide pre-oxidation of chironomid larvae metabolites followed by chlorination. Issue 59 (19th December 2016) - Song, Biyao; Sun, Xingbin; Jiang, Yifeng; Li, Yanpeng; Che, Lu
Abstract: The objective of this research was to investigate the formation of disinfection by-products (DBPs) during chlorine dioxide pre-oxidation of chironomid larvae metabolites followed by chlorination. The mode of action of chlorine dioxide/chlorine combination was clarified, including the impact of different factors on DBP formation. The results indicated that pre-oxidation suppressed the production of most DBPs such as trihalomethanes, haloacetic acids, haloacetonitriles, and haloketones, compared to when chlorination was used alone. The concentrations of trichloromethane (TCM), dichloroacetic acid (DCAA), trichloroacetic acid (TCAA), dichloroacetonitrile (DCAN), and 1, 1-dichloro-2-propanone (1, 1-DCP) decreased with prolonged pre-oxidation times, with the highest yields observed for DCAA and TCAA. The solution pH had a distinct influence on DBP formation, with the concentrations of DCAA, TCAA, DCAN, 1, 1-DCP, and 1, 1, 1-trichloro-2-propanone (1, 1, 1-TCP) initially increasing and then decreasing with increasing pH. The maximum concentrations of DCAA and TCAA were observed at pH 7–8, whereas the TCM content increased continuously on increasing the pH up to 8–9. Other DBPs reached their maxima at pH 6–7. Regarding thermal effects, the formation of 1, 1, 1-TCP enhanced at higher temperatures, while the concentrations of DCAN, 1, 1, -DCP, and TCM first increased between 10 and 20°C and then decreased between 20 and 30°C. The concentrations of DCAA and TCAA decreased from 10 to 20°C and then increased between 20 and 30°C.